Impact of Consumer Loss Aversion on Operations in the Context of Remanufacturing - Bi-feng Liao; Bing-zhang Wang (Complexity)
Loss aversion is an important psychological characteristic that has become well supported in finance and marketing. This paper introduces consumer loss aversion into the game model with two substitutable products in a remanufacturing system. The loss-averse consumers gain utility from comparing the price and value dimensions with the superior product. Our model highlights alternative products competition, product selections, and consumption psychology in a remanufacturing environment. The results show that consumer loss aversion has important implications on key decisions in the remanufacturing system. When the manufacturer faces loss-averse consumers, there is a tendency to charge higher prices for two types of products. At the same time, the sales prices increase with the degree of loss aversion. Further analysis reveals that if the manufacturer manipulates consumers with a high probability of purchase, the feature of loss aversion usually benefits him. Our theoretical analyses are proven by numerical computation and some useful conclusions are summarized in this paper.